DAMPAK KENDARAAN PARKIR DI BADAN TERHADAP KAPASITAS JALAN BASUKI RAHMAT KOTA BENGKULU - Samsul Bahr; Makmun R. Razali; Novilidia Novilidia (Universitas Bengkulu, 2019)
Availability of parking is a very important infrastructure in the transportation system. On-street parking Is one of the causes of traffic congestion if its management is not appropriate. Basuki Rahmat Street is one of Bengkulu city’s governmental centers, that’s why on road parking conditions in Basuki Rahmat Street will be important to be researched and studied. The purpose of this study is to know about Basuki Rahmat Street performance and determine the level of traffic flow density due to the use of the road as a parking lot. Methods and techniques of data collectionare done directly in the field. From the results of the study for 4(Four) days of observations is obtained the data on the number of light vehicles (LV) by 52 % and 48 % of motorcycle. If seen from the side barriers, the contribution of parked vehicles on the percentage of side friction is 91% in Saturday, 0% in Sunday, 71% in Monday and 81% in Tuesday, and by reviewing the component of side friction is appearing that vehicles which parked in Basuki Rahmat Street area doesn’t make the road’s performance decreased. It can be seen from the value of the degree of saturation which is 0.38<0.75 as required by Indonesian Highway Capacity Manual. Actual average capacity of 4864.86 smp /hour for Saturday and Sunday,and 4782.96 smp / hour for Monday and Tuesday, This capacity value is smaller than the basic capacity of undivided two-lane road that is equal to 6000 smp /hour. It shows that Basuki Rahmat Street is still able to accommodate the traffic that passes through the road. Traffic conditions at peak hours at Basuki Rahmat Street is specified based on the degree of saturation (DS), that the performance on the road Basuki Rahmat for 4 days observations is at B level, which means that the flow is stable with moderate traffic volume and where the speed is begin to be restricted by the traffic condition, and the driver still free enough to choose the speed and lane road to be used.